Collision detection with V-Collide and PhysX libraries for virtual interaction with haptic interfaces - Pinto-Salamanca, María Luisa; Sofrony-Esmeral, Jorge Ivan; Jiménez, Daniel Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Integration of haptic devices in virtual training applications is a complex task that requires the integration of a variety of software libraries. This paper concentrates on exploring the performance of different collision detection algorithms that will allow the real-time manipulation of mixed (superficial/volumetric) 3D virtual models, and hence the geometric manipulation of these objects in a virtual scene. Using open source software tools, a three-dimensional environment was developed with the potential interaction of force feedback and interaction within virtual components. Virtual interaction tests are presented with two haptic devices, measuring initialization times, frame rates and consumption of RAM. The results allow selecting the PhysX library compared to the V-Collide library, for analysis of collision detection in a virtual environment with tactile feedback.